2013
DOI: 10.1007/s00253-013-4737-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periplasmic oxidation of glucose on pyoverdine synthesis in Pseudomonas putida S11

Abstract: Fluorescent pseudomonads catabolize glucose simultaneously by two different pathways, namely, the oxidative pathway in periplasm and the phosphorylative pathway in cytoplasm. This study provides evidence for the role of glucose metabolism in the regulation of pyoverdine synthesis in Pseudomonas putida S11. We have characterized the influence of direct oxidation of glucose in periplasm on pyoverdine synthesis in P. putida S11. We identified a Tn5 transposon mutant of P. putida S11 showing increased pyoverdine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Besides, the production of chelating substances H 2 S, CO 2 , mineral acids, siderophores, biologically active substances like indole acetic acid [119], gibberellins and cytokinins Penicillium bilaii Citric and oxalic acid [105] Penicillium regulosum Citric and gluconic acid [106] Pseudomonas aeruginosa Gluconic [97] Pseudomonas putida Gluconic acid [107] Pseudomonas sp. Citric, gluconic [108] Pseudomonas sp.…”
Section: Other Theories Of Mineral Phosphate Solubilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the production of chelating substances H 2 S, CO 2 , mineral acids, siderophores, biologically active substances like indole acetic acid [119], gibberellins and cytokinins Penicillium bilaii Citric and oxalic acid [105] Penicillium regulosum Citric and gluconic acid [106] Pseudomonas aeruginosa Gluconic [97] Pseudomonas putida Gluconic acid [107] Pseudomonas sp. Citric, gluconic [108] Pseudomonas sp.…”
Section: Other Theories Of Mineral Phosphate Solubilizationmentioning
confidence: 99%
“…The characterization of different phosphate solubilizing bacteria has shown that direct oxidation pathway provides the biochemical basis for highly efficacious phosphate solubilization in Gram negative bacteria via diffusion of the strong organic acids like gluconic acid produced in the periplasm into the adjacent environment [59,[93][94][95]101,103,107]. Glucose is the precursor for synthesis of gluconic acid [122].…”
Section: Genetics Of Direct Oxidation Pathway and Organic Acid Producmentioning
confidence: 99%
“…The upregulation of the pqq and gcd genes in the gacS mutant was confirmed by qPCR (not shown). In Pseudomonas and other Gram‐negative bacteria, gluconic acid biosynthesis has been shown to be dependent on PQQ as an enzymatic cofactor of the membrane‐bound quinoprotein, glucose dehydrogenase (Gcd) (Goldstein, ; Kaur et al ., ; de Werra et al ., ; Kremmydas et al ., ; Ponraj et al ., ). Gcd acts as a glucose sensor and catalyses glucose into gluconic acid by periplasmic oxidation.…”
Section: Resultsmentioning
confidence: 97%
“…Gcd acts as a glucose sensor and catalyses glucose into gluconic acid by periplasmic oxidation. A consecutive oxidation reaction converts gluconic acid to 2-keto gluconic acid (Schleissner et al, 1997;de Werra et al, 2009;Ponraj et al, 2013). This study showed, for the first time, that a mutation in the Gac-system of P. fluorescens SBW25 led to a significant transcriptional up-regulation of pqq biosynthesis genes and gcd gene.…”
Section: Resultsmentioning
confidence: 73%
“…The up-regulation of the pqq and gcd genes in the gacS mutant was confirmed by qPCR (not shown). In Pseudomonas and other Gram-negative bacteria, gluconic acid biosynthesis has been shown to be dependent on PQQ as an enzymatic cofactor of the membrane bound quinoprotein, glucose dehydrogenase (Gcd) Kaur et al, 2006;de Werra et al, 2009;Kremmydas et al, 2013;Ponraj et al, 2013). Gcd acts as a glucose sensor and catalyses glucose into gluconic acid by periplasmic oxidation.…”
Section: Resultsmentioning
confidence: 99%